Analysis Of Warehouse Management and Implementation of Barcodes for Monitoring Goods at PT XYZ: Analisis Manajemen Pergudangan dan Penerapan Barcode untuk Monitoring Barang di PT XYZ - Sya Ilma Marta; Minto Waluyo (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
PT XYZ is a company that operates in the state electricity generation sector. One of the keys to success and supporting the company's smooth operations is good warehouse management to reduce management errors. This study was carried out as an effort to improve warehouse management so that it can increase the company's operational efficiency. The failure mode and effect analysis method approach is a methodology used to evaluate failures that occur in a system, design, process or service. After carrying out the analysis, the results showed that the biggest failure was stock taking per item <5 minutes with the biggest point being 288 which was caused by manual stock taking activities. The suggestion for improvement given is the application of Barcodes (QR Codes) to simplify the stock taking process and shorten the stock taking work time. By implementing the QR Code system, warehouse management can cut the stock opname working time from what was previously done > 5 minutes to a maximum of 3 minutes with a total duration of work of around 1 month.